2017
DOI: 10.3389/fpls.2017.00938
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Differentially Expressed Genes Induced by Low and High Potassium Levels Provides Insight into Fruit Sugar Metabolism of Pear

Abstract: Potassium (K) deficiency is a common abiotic stress that can inhibit the growth of fruit and thus reduce crop yields. Little research has been conducted on pear transcriptional changes under low and high K conditions. Here, we performed an experiment with 7-year-old pot-grown “Huangguan” pear trees treated with low, Control or high K levels (0, 0.4, or 0.8 g·K2O/kg soil, respectively) during fruit enlargement and mature stages. We identified 36,444 transcripts from leaves and fruit using transcriptome sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 76 publications
2
25
0
Order By: Relevance
“…The 17 DEGs included nine Cytochrome P450 family members, four oxidoreductase family members, two 1-aminocyclopropane-1-carboxylate oxidase family members, one Omega-6 fatty acid desaturase, and one S-norcoclaurine synthase (Table S15). The oxidoreductase activity enrichment also had reported in other plants treated by low nutrient stresses, such as in low potassium treated pear fruit [34], in low nitrogen treated wheat [35], in low phosphorus treated sorghum [36]. The networks of the DEGs in profile 1 were conducted, and the results revealed that CYP51, a member of cytochrome P450 family was the hub gene with the highest node degree 8 (Figure 6B, Tables S5 and S6).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The 17 DEGs included nine Cytochrome P450 family members, four oxidoreductase family members, two 1-aminocyclopropane-1-carboxylate oxidase family members, one Omega-6 fatty acid desaturase, and one S-norcoclaurine synthase (Table S15). The oxidoreductase activity enrichment also had reported in other plants treated by low nutrient stresses, such as in low potassium treated pear fruit [34], in low nitrogen treated wheat [35], in low phosphorus treated sorghum [36]. The networks of the DEGs in profile 1 were conducted, and the results revealed that CYP51, a member of cytochrome P450 family was the hub gene with the highest node degree 8 (Figure 6B, Tables S5 and S6).…”
Section: Discussionsupporting
confidence: 73%
“…The networks of the DEGs in profile 1 were conducted, and the results revealed that CYP51, a member of cytochrome P450 family was the hub gene with the highest node degree 8 (Figure 6B, Tables S5 and S6). In low potassium treated pear fruit, there multiple cytochrome P450 members were detected [34]. In low potassium treated tobacco, 3 cytochrome P450 members were also up-regulated [37].…”
Section: Discussionmentioning
confidence: 95%
“…In cotton, K + deficiency resulted in premature leaf senescence as a result of higher H 2 O 2 and malondialdehyde content ( Hu et al, 2016 ). Genes related to peroxidase metabolism were down-regulated in pear grown under K + deficiency, indicating that under high K + , the accumulation of excessive oxygenated compounds was held in check by greater peroxidase activity ( Shen et al, 2017 ). In grapevines, soil application of K + to plants grown under drought stress enhanced antioxidant enzyme activity in the leaves ( Haddad and Kamangar, 2016 ).…”
Section: K + Ros and Plant Stressmentioning
confidence: 99%
“…In fruits, the deficiency of this macronutrient decreases the glucose, fructose, and sucrose levels, and in plants of Rosaceae family, it decreases sorbitol levels [90], and in species with large amounts of lycopene such as tomato [91], there is less red color intensity due to reduction in the synthesis of this pigment [60,64].…”
Section: Potassium Deficiency and Toxicity Symptoms In Vegetablesmentioning
confidence: 99%